ONLINE SURVEY MENGENAI PENGARUH KUALITAS WEBSITE, REPUTASI PERSEPSIAN DAN CUSTOMER TRUST TERHADAP NIAT BERTRANSAKSI DI ELECTRONIC COMMERCE - , Muhammad Andryzal Fajar, SE., Dr. Didi Achjari, M.Com. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research aims to provide empirical evidence on the effect of website quality, perceived reputation and customer trust on intention to transact in electronic commerce through online surveys. The research was conducted using an online questionnaire survey with 166 respondents. Data were analyzed using PLS (Partial Least Square) with the program smartPLS 2.0. The results of this research show the website quality is the perceived system quality and perceived service quality positive effect on perceived reputation and customer trust. Website with high quality will increase user trust while reputation will reduce uncertainty and increase trust. However, the effect of perceived information quality no significant on customer trust. The information quality in terms of accuracy, ease of understanding, usefulness, completeness, relevance and up to date has not been enough to establish trust of customer. Perceived reputation positive effect on customer trust. Shows e-commerce is perceived as a reputable party would lead trust. Perceived reputation and customer trust positive effect on intention to transact in ecommerce. Shows the website reputation plays a role in the intention to transact and trust is an important factor in whether customer will consider transactions in ecommerce.